PENGARUH PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI TAHUN 2003-2021 - Siregar, Syahdan Abdul Haris (Journal of Development Economic and Social Studies, 2023)
Regional Original Income (PAD) is a source of income that must be maximized in order to improve the welfare of the community through management carried out by local governments. PAD encourages economic growth due to its function as one of the fiscal components of local governments in equitable distribution of regional development and income distribution for local communities that can accelerate economic activities and consumption to increase GRDP. This study aimed to see the effect of local revenue on economic growth in Districts/Cities in Gorontalo Province. Regional original income consisting of regional taxes, regional levies, results of regional wealth management, and other legitimate income. This research used panel data regression analysis with Fixed Effect Model method. According to this study, the result revealed that local taxes, regional wealth management outcome, and other legitimate income have a significant effect on economic growth. Furthermore, the regional levy variable has no significant effect on economic growth of the Districts/Cities in Gorontalo Province during the period 2003 to 2021. Keywords: Regional Original Income, Economic Growth, Fiscal Decentralization